ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RGEC DAN DAMPAKNYA TERHADAP PENINGKATAN JUMLAH NASABAH - Devika Cherly Putrihadiningrum (Universitas Nahdlatul Ulama Sidoarjo, 2021)
Covid-19 has an impact on the weak economy of the community, banking sector is a sector that helps improve the economy of the community in the midst of the covid-19 pandemic. The level of health of the bank is in the interests of all relevant parties, both owners, bank administrators, community users of bank services, Bank Indonesia applies bank supervision authority or other parties. If the bank's assessment is declared